Synthesis of novel molybdaboranes from (eta(5)-C5R5)MoCln precursors (R=H,Me; n=1,2,4) - Aldridge, S; Shang, M; Fehlner, T (American Chemical Society, 1998)
Reaction of Cp*MoCl4(1), or (Cp*MoCl2)2 (2), Cp* = η5-C5Me5, with BH3·THF ultimately generates the Mo(II) cluster (Cp*Mo)2B5H9 (7), together with the Mo(III) species (Cp*MoCl)2B4H10, 4. Prereduction of 2 before reaction with BH3·THF yields only 7. The structure of 4 consists of two Cp*Mo units bridged by two chlorides and a [B2H5(B2H5)]2- ligand in which the two diboron moieties are connected by a B-B-B three center bond. Closer inspection of the reaction by 11B and 1H NMR reveals the existence of three intermediate species (Cp*MoCl)2B2H6 (3), (Cp*MoCl)2B3H7 (5), and (Cp*Mo)2(B2H6)2 (6). Each of these species has been characterized spectroscopically, and crystal structures have been obtained for 3 and 5. Compound 3 features molybdenum centers bridged by two chlorides and an ethane-like [B2H6]2- ligand such that the B-B bond is perpendicular to the Mo-Mo bond. Replacing one terminal H by [B2H5] generates 4. The structure of 5 is based on a trigonal bipyramidal Mo2B3 core, and the molecule is electronically unsaturated although the Mo-Mo distance (3.096 Å) precludes the existence of multiple bonding between the metal centers. 5 exists as a relatively stable molecule despite having too few electrons and too few atoms to adopt a capped structure based on a polyhedron with fewer vertexes. Comparison of MO descriptions of the electronic structure of 5 with that of the later transition metal species (Cp*Co)2B3H7 (8) shows that this stabilization is derived from the appropriate energy match between Cp*Mo and borane based orbitals which elevates the energy of the Mo-B antibonding LUMO, a cluster orbital which would normally be filled, into the region of unoccupied orbitals. The concentration vs time behavior for the final products 4 and 7, for the intermediates 3, 5, and 6, for the monoboron species BH3·THF and BH2Cl, and selected non-boron containing species is used to define a pathway for the molybdaborane cluster condensation. With 1, use of LiBH4 as the monoboron source yields 6 as the primary product via 3 as an intermediate, whereas prereduction of 2 with [Et3BH]- results in the formation of 7. The varied cluster building abilities of BH3·THF vs LiBH4 originate in the differing reduction and coordination properties of the two monoboranes. Investigation of the analogous Cp = η5-C5H5 system reveals similar chemistry albeit simpler and on a shorter time scale.